LAW ENFORCEMENT OF ILLEGAL FISHING IN THE IMMIGRATION PERSPECTIVE IN THE WORKING AREA OF BELAWAN IMMIGRATION OFFICE - Muhammad Alvi Syahrin; Tony Mirwanto; Cornelius Agatha Gea (Journal of Law and Border Protection, 2023)
The abundance of natural resources and the vast area of ​​the ocean in Indonesia are an attraction for the surrounding countries. This makes the case of Illegal fishing a case that is often found in Indonesian seas. One of the affected areas is Belawan seas. Based on the supervision carried out by the Ministry of Maritime Affairs and Fisheries (KKP), it is stated that illegal fishing violations often occur in EEZ (Exclusive Economic Zone) seas. One of the institutions authorized to enforce the law on illegal fishing is immigration. This study aims to see the implementation of law enforcement and immigration law strategies against foreigners who commit illegal fishing crimes in the work area of ​​the Belawan Immigration Office. This research is structured using a combination of normative and empirical research with qualitative methods using the basic theory of State Sovereignty and Effectiveness (Enforcement) of Law. The results of the study found that the Belawan Immigration Office carried out law enforcement in the form of Immigration Administration Actions namely deportation, some of the obstacles encountered in law enforcement were the lack of infrastructure in the form of ships and the limited detention room at the Medan Immigration Detention Center. The researchers also found that the legal strategy efforts carried out by the Belawan Immigration Office were preventive and repressive strategies. With Preventive Strategies in the form of coordination with Foreign Surveillance Team and Foreign Embassies, Repressive Strategies in the form of strengthening the intensity of Immigration Administrasion Action and Investigations.